The Meaning of Poetry Set of Ca Leleng Do, Do Leleng Ca by Inosensius Sutam - Jeharu, Maria Sulastri; Supriyanto, Teguh (Pascasarjana Universitas Negeri Semarang, 2018)
Ca Leleng Do, Do Leleng Ca (One is equal to many, many is equal to one) poetry set is a traditional poetry originating from Manggarai, by Inosensius Sutam. This study has purpose to describe and explain the meanings of the poetry set. The approach uses in this study is theoretical and methodological approach. The theoretical approach used is semiotic. Meanwhile the methodological approach is qualitative descriptive. The technique of collecting the data is done by literature reviews and heuristic reading. Then, the validity of the data is gained through deeper observation and data triangulation. The technique of analyzing data is done by semiotic model. Based on the research, the poetry set contains meaning related to Manggarai’s people lifes, such as (1) unity and union meaning created in inter-relationship and social environment, (2) empirical meaning bind from ancestors’ relationship, (3) patriotism.